225k views
1 vote
Solve for x: 11x+6=6x+11​

1 Answer

0 votes


\longrightarrow{\green{ x\:=\:1}}


\sf \bf {\boxed {\mathbb {Step-by-step\:explanation:}}}


11x + 6 = 6x + 11


\: 11x - 6x = 11 - 6


\: 5x = 5


\: x = (5)/(5)


\: x = 1

Therefore, the value of
x is 1.


\sf \bf {\boxed {\mathbb {To\:verify:}}}


11 * 1 + 6 = 6 * 1 + 11


\: 11 + 6 = 6 + 11


\: 17 = 17

➼ L. H. S. = R. H. S

Hence verified.


\large\mathfrak{{\pmb{\underline{\orange{Mystique35 }}{\orange{❦}}}}}

User Bsisco
by
4.8k points